Criibacterium bergeronii gen. nov., sp. nov., a new member of the family Peptostreptococcaceae, isolated from human clinical samples. Issue 3 (15th March 2021) - Maheux, Andrée F.; Boudreau, Dominique K.; Abed, Jehane Y.; Bérubé, Ève; Brodeur, Stéphanie; Bernard, Kathryn A.; Hashimi, Ameena; Ducrey, Éloïse; Guay, Émilie F.; Raymond, Frédéric; Corbeil, Jacques; Domingo, Marc-Christian; et al.
Abstract : A rod-shaped, motile anaerobic bacterium, designated CCRI-22567 T, was isolated from a vaginal sample of a woman diagnosed with bacterial vaginosis and subjected to a polyphasic taxonomic study. The novel strain was capable of growth at 30–42 °C (optimum, 42 °C), at pH 5.5–8.5 (optimum, pH 7.0–7.5) and in the presence of 0–1.5 % (w/v) NaCl (optimally at 0.5 % NaCl). The phylogenetic trees based on 16S rRNA gene sequences showed that strain CCRI-22567 T forms a distinct evolutionary lineage independent of other taxa in the family Peptostreptococcaceae . Strain CCRI-22567 T exhibited 90.1 % 16S rRNA gene sequence similarity to Peptoanaerobacter stomatis ACC19a T and 89.7 % to Eubacterium yurii subsp. schtitka ATCC 43716. The three closest organisms with an available whole genome were compared to strain CCRI-22567 T for genomic relatedness assessment. The genomic average nucleotide identities (OrthoANIu) obtained with Peptoanaerobacter stomatis ACC19a T, Eubacterium yurii subsp. margaretiae ATCC 43715 and Filifactor alocis ATCC 35896 T were 71.8, 70.3 and 69.6 %, respectively. Strain CCRI-22567 T contained C18 : 1  ω9 c and C18 : 1  ω9 c DMA as the major fatty acids. The DNA G+C content of strain CCRI-22567 T based on its genome sequence was 33.8 mol%. On the basis of the phylogenetic, chemotaxonomic and other phenotypic properties, strain CCRI-22567 T is considered to represent a new genus and species within the family Peptostreptococcaceae, for which the name Criibacterium bergeronii gen. nov., sp. nov., is proposed. The type strain of Criibacterium bergeronii is CCRI-22567 T (=LMG 31278 T =DSM 107614 T =CCUG 72594 T ).